If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-3p=(-5)(3+2p)
We move all terms to the left:
13-3p-((-5)(3+2p))=0
We add all the numbers together, and all the variables
-3p-((-5)(2p+3))+13=0
We multiply parentheses ..
-3p-((-10p-15))+13=0
We calculate terms in parentheses: -((-10p-15)), so:We get rid of parentheses
(-10p-15)
We get rid of parentheses
-10p-15
Back to the equation:
-(-10p-15)
-3p+10p+15+13=0
We add all the numbers together, and all the variables
7p+28=0
We move all terms containing p to the left, all other terms to the right
7p=-28
p=-28/7
p=-4
| 3x+63=-9x-9 | | x+(x-4)^2-6=0 | | 3(5x+2)=6x-15 | | -(3/8)h=9 | | 6x-9=2x-3) | | x+3=+2x-1 | | 2x+30=6x-74= | | 45=17-2c | | 63+17x-10x^2=2x^2+16x | | 2x+5(-x)-5=0 | | 10/x+10=1 | | (x+5)+(4x-4)+(3x-1)=180 | | 4x+15+1x=87 | | 2x+3x=90. | | a/5-a/10=1/2 | | -99=12(z-3)+9z | | 39=77-x | | -9m+-m+15m+10m=16 | | 4(x-1)=4x-10+6 | | 6x-9=3(2x=2) | | x+x-18+x-20=88 | | 7x+36=x+6 | | 20x-70=180 | | 12/x=48/4 | | 6x-6x+5x-2x=12 | | 52-g=22 | | -2(j-8)=4 | | 4(3x-2)/2=14 | | 7x+7+8x=-23 | | 44=29+k | | 15y-9y+y-2y+4y=18 | | |–4d+6|=12 |